2018
DOI: 10.1515/pjfns-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Buckwheat Water Biscuits Formulated from Fermented Flours by Selected Lactic Acid Bacteria

Abstract: The growth of lactic acid bacteria during liquid-state fermentation of buckwheat fl our and changes in pH during the process were analyzed. Eight strains of Lactobacillus were selected as the most active strains used to obtain new fermented fl ours. Physical properties of buckwheat water biscuits formulated from these fermented fl ours were studied.The hardness of freshly prepared biscuits was affected by the lactic acid bacteria applied, with its highest value noted for the water biscuits made of buckwheat fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…The results indicate that the baking conditions, physical structure of BBs, and interactions of the digestive fluid are important factors affecting the expanded bioaccessibility of Ru and Q. This is in accordance with our recent study demonstrating the impact of selected LAB on some physical properties of BBs prepared from fermented buckwheat flour [ 17 ].…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results indicate that the baking conditions, physical structure of BBs, and interactions of the digestive fluid are important factors affecting the expanded bioaccessibility of Ru and Q. This is in accordance with our recent study demonstrating the impact of selected LAB on some physical properties of BBs prepared from fermented buckwheat flour [ 17 ].…”
Section: Resultssupporting
confidence: 91%
“…The raw and roasted buckwheat flour were pretreated to reduce microbial populations before the fermentation process as described in detail by Wronkowska et al [ 17 ]. In brief, about 50 g of flour was suspended in 950 mL of distilled water, heated at 90 °C for 45 min, then autoclaved at 121 °C/15 min and finally cooled to 37 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors suggested that intact buckwheat proteins could acquire the ability to inhibit ACE after being consumed and can then be subjected to gastrointestinal digestion. Also, the physical structure of biscuits seems to be important as the impact of select bacteria on some physical properties of the water biscuits prepared from fermented buckwheat flour was previously demonstrated [28]. In summary, the bioaccessible ACE inhibitory activity from biscuits formulated from fermented buckwheat flours was found to be high.…”
Section: The Bioaccessible Ace Inhibitory Activity Of Biscuits Formulmentioning
confidence: 80%
“…Commercially available flour obtained from Polish common buckwheat ( Fagapyrum esculentum Moench) was purchased from a local industry plant (Melvit S.A., Kruki, Poland). The fermentation process and preparation of buckwheat biscuits were carried out as described by Wronkowska et al [ 28 ] and Zieliński et al [ 29 ]. All bacteria used in this study originated from the Institute of Animal Reproduction and Food Research Polish Academy of Sciences collection, with one exception for L. rhamnosus GG, which was purchased from ATCC ® .…”
Section: Methodsmentioning
confidence: 99%